(untitled) (Homoeopathy for All, 2024)
The skin, which is frequently referred to as the "mirror of the soul," is a reflection of both our internal and external health. This principle is the cornerstone of the homeopathic treatment of cutaneous abnormalities, such as warts, moles, etc. Warts are prevalent skin growths that can manifest on a variety of body regions, including the palms, feet, and mucous membranes, as a result of an infection with the human papillomavirus (HPV). They are classified according to their location—common warts around nails and digits, foot warts, and genital warts—as well as their morphology and texture, which can be fuzzy, firm, flat, smooth, scratchy, or leathery. These growths are highly contagious and can be transmitted through direct cutaneous contact or indirectly through contaminated surfaces. In the Indian context, warts hold particular cultural and medical significance, with various beliefs and myths influencing their perception and treatment.